Patient adherence and preference considerations in managing cardiovascular risk: focus on single pill and amlodipine/atorvastatin fixed combination - Aslam, Farhan (Dove Medical Press, 2009)
Cardiovascular disease (CVD) accounts for in excess of 930,000 deaths in the United States each year. Risk factors for CVD often co-exist. Studies estimate that over half of the hypertensive population also has dyslipidemia. Observational data suggest that fewer than 10% of patients attain recommended therapeutic targets for both conditions. A variety of patient, regimen and system characteristics have been associated with the risk for non-adherence. Poly-pharmacy and complex drug regimens are associated with poor patient adherence and thus the use of fixed-dose combination therapies, may improve adherence by reducing the pill burden. The fixed-dose combination of amlodipine/atorvastatin offers a convenient and effective approach to manage two important CVD risk factors. The combination of amlodipine/atorvastatin has a synergistic effect. The half-life of both agents facilitates once-daily dosing and both can be administered at any time of the day with or without food. Amlodipine/atorvastatin combined pill can be used to initiate both agents or patients can be switched directly from single-agent therapy with one or both agents. The convenience of single-pill amlodipine/atorvastatin has the potential to improve patient adherence and the management of cardiovascular risk in selected patients, thereby improving clinical outcomes.